2008
DOI: 10.1016/j.jfms.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Pinch-induced behavioral inhibition (‘clipnosis’) in domestic cats

Abstract: Research has documented immobilization of rodents, rabbits, guinea pigs and dogs by mechanical means, typically using neck clips or inversion ('animal hypnosis'). In contrast, only a few studies of mechanical immobilization of cats are available, although some success has been reported in the literature. Domestic cats may be effectively immobilized by clips placed along the animal's dorsum. We use the term 'pinch-induced behavioral inhibition' (PIBI) for this behavior because it describes both the method and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
1
15
1
Order By: Relevance
“…In contrast, tonic immobility is induced by inverting the animals and pressing them down [16,22]; dorsal immobility is induced when the animals are firmly grasped [23] or by tightly bandaging around the neck [14]; 3) the Transport Response does not require the vestibular input as shown in our previous study of labyrinthectomized mouse pups [6]. On the other hand, vestibular stimulation is necessary for dorsal immobilization in adult rats [24]; and 4) the remarkable pliability of the trunk during the Transport Response are the opposite of the motor rigidity in the dorsal and tonic immobility [15,18]; 5) the eyelids are rather closed in our study as well as in the previous anecdotal observations in the Transport Response, while the eyelids are widely opened in the dorsal ([18,24]) and the clamp-induced immobility ([25,26]). These data consistently suggested that the Transport Response is a distinct type of immobilization from dorsal or tonic immobility.…”
Section: Discussionsupporting
confidence: 53%
“…In contrast, tonic immobility is induced by inverting the animals and pressing them down [16,22]; dorsal immobility is induced when the animals are firmly grasped [23] or by tightly bandaging around the neck [14]; 3) the Transport Response does not require the vestibular input as shown in our previous study of labyrinthectomized mouse pups [6]. On the other hand, vestibular stimulation is necessary for dorsal immobilization in adult rats [24]; and 4) the remarkable pliability of the trunk during the Transport Response are the opposite of the motor rigidity in the dorsal and tonic immobility [15,18]; 5) the eyelids are rather closed in our study as well as in the previous anecdotal observations in the Transport Response, while the eyelids are widely opened in the dorsal ([18,24]) and the clamp-induced immobility ([25,26]). These data consistently suggested that the Transport Response is a distinct type of immobilization from dorsal or tonic immobility.…”
Section: Discussionsupporting
confidence: 53%
“…A variety of vertebrate species have what are termed “hypnotic responses” to external stimuli (Gallup, Jr., 1974). Animal hypnosis is defined as a behavioural state where the animal is immobilised and desensitised to external stimuli (Fleischmann et al, 1988; Pozza et al, 2008). Although this can be achieved in several ways, in mammals, immobilisation can be induced by pinching or clipping the skin at certain sites, such as the neck (Pozza et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In rabbits, positioning the animal on its back can produce immobilization for several minutes (Viala et al 1978). In cats, it has been documented that immobilization can be induced by placing clips along the dorsal midline, principally at the cervical level (Pozza et al 2008). This technique is frequently used in veterinary practice to gently restrain cats, although its efficiency varies across cats (Pozza et al 2008).…”
Section: Distributed and Localized Effectsmentioning
confidence: 99%